Endoscopic combined “transseptal/transnasal” approach for pituitary adenoma: reconstruction of skull base using pedicled nasoseptal flap in 91 consecutive cases - Yasunori Fujimoto; Leonardo Balsalobre; Fábio P. Santos; Eduardo Vellutini; Aldo C. Stamm (Arquivos de Neuro-Psiquiatria)
Objective The purpose of this study was to describe the endoscopic combined “transseptal/transnasal” approach with a pedicled nasoseptal flap for pituitary adenoma and skull base reconstruction, especially with respect to cerebrospinal fluid (CSF) fistula.Method Ninety-one consecutive patients with pituitary adenomas were retrospectively reviewed. All patients underwent the endoscopic combined “transseptal/transnasal” approach by the single team including the otorhinolaryngologists and neurosurgeons. Postoperative complications related to the flap were analyzed.Results Intra- and postoperative CSF fistulae were observed in 36 (40%) and 4 (4.4%) patients, respectively. Among the 4 patients, lumbar drainage and bed rest healed the CSF fistula in 3 patients and reoperation for revision was necessary in one patient. Other flap-related complications included nasal bleeding in 3 patients (3.3%).Conclusion The endoscopic combined “transseptal/transnasal” approach is most suitable for a two-surgeon technique and a pedicled nasoseptal flap is a reliable technique for preventing postoperative CSF fistula in pituitary surgery.